Effects of quality of life on the price of real estate in Vilnius city - Burinskienė, Marija; Rudzkienė, Vitalija; Venckauskaitė, Jūratė (International Journal of Strategic Property Management, 2011)
The urban development covers the consensus of a wide range of activities and is aimed at equivalent coordination of the impact of economic, social and environmental factors on planning. Due to different attitudes and interests planners and scientists find it rather complicated to come to a common and widely acceptable attitude towards urban development patterns through harmonization of forms and development principles. The paper includes the theoretical attitudes, related to future insights, into the urban development conceptions. Moreover, assessing the impact of the economic paradigms on urban visions, the paper analyses the influence of development concepts on the qualities of development forms as well as on the creation of future urban alternative visions, compatibility with the principles of sustainable development and proper quality of life. The price of real estate is addressed as one of the key social indicators and the ones that reflect the quality of life. The theoretical provisions, with the help of expert evaluation, are verified taking the districts of Vilnius as an example and considering qualities and forms, population, jobs, area, noise level and pollution of individual districts on the basis of different components. Conceptual modelling principles are applied to determine critical values of the indicators that characterize the sustainable development. Based on them, a system is created that helps to define features of individual urban districts,potential development alternatives and achievable allowed marginal values of the quality of life.First Publish Online: 5 Oct 2011